COPPING STRES Di RT.007/RW.01 Kelurahan Banteng Kecamatan Nusaniwe - Doan Huliselan; Junus Kwelju (Fakultas Ilmu Sosial dan Ilmu Politik, 2023)
Coronavirus, also known as COVID-19, is a virus that spreads rapidly from person to person. Sources of data recorded from the Maluku Province Covid-19 Task Force on September 19, 2022, who were treated were 18,798 people and those who were confirmed died were 301 people and those who were confirmed recovered were 18,468 people. The purpose of this study was to find out and analyze about providing an overview of cases of Coping Stress Domestic Violence by a husband against his wife in RT.007/ RW.01 Kelurahan Benteng. This research is a qualitative research. The target in this research is the people who live in RT. 007/RW.01 Benteng Village, Nusaniwe District. There were 6 researchers (5 clients and 1 RT). Research instruments include observations, attachments to case study interviews that have been prepared, recording devices, and notebooks. The results found were physical violence, among others, happened to Informants W.J, E.R, and Y.L were slapping, hitting, spitting, pulling hair (picking), kicking, cornering with cigarettes, hitting/injuring, and so on. Usually this treatment looks like blue-blue, bruised face, broken teeth or other scars. Psychological or emotional violence is an act that causes fear, loss of self-confidence, loss of ability to act, feeling helpless and or severe psychological suffering on informants W.J, E.R, Y.L and L.W. Sexual violence, according to the informants W.J, E.R, Y.L and L.W, is a type of violence that includes (removing) the wife from her inner needs, forcing sexual intercourse, forcing her own sexual appetite, not paying attention to the wife's satisfaction. Economic violence, Informants W.J, E.R, Y.L, L.W and J.F that what is meant is work that is very difficult and occurs in the Covid-19 masses which causes income to decrease and the household is very abnormal. Conclusion: Acts of domestic violence such as actions that cause pain, illness or serious injury that occurred to informants W.J, E.R, and Y.L such as slapping, hitting, etc. resulted in informants W.J, E.R, Y.L, and L.W feeling fear, loss of self-confidence, loss of ability to act. Sexual violence also occurred for informants W.J, E.R, Y.L and L.W. This violence was like keeping the wife away from her inner needs and not paying attention to the satisfaction of the wife, but what became the main problem of informants W.J, E.R, Y.L, L.W, and J.F, namely economic violence due to work which is very difficult and happened during the Covid-19 mass which resulted in decreased family income. Suggestions for more routine socialization of the RT rules regarding domestic violence so that people obey the rules.